The Mediating Role of Innovative Behavior in The Effect Of Liberal Leadership on Business Performance (Third Sector Social Economic Review, 2025)
This research aims to examine the effect of liberal leadership style on employees' job performance and the mediating role of innovative behavior in this relationship. Digitalization, rapid change and increasing competition have directed organizations to leadership approaches that encourage innovation. Based on this point, this study analyzes the effect of liberal leadership, which grants employees a high level of autonomy, on innovative behavior and job performance. The data of the research were collected through a survey from 403 individuals working in SMEs operating in various sectors in Kars province and evaluated with the structural equation modeling (SEM) method using the Smart-PLS statistical analysis application. While the diversity of the participants increased the generalizability of the research, the data were confirmed to be sufficient in terms of academic validity and reliability by the statistical tests conducted within the scope of the research. The findings reveal that there is a significant and positive relationship between liberal leadership and job performance, and that liberal leadership has a highly significant effect on innovative behavior. In addition, the findings indicate that the relationship between innovative behavior and job performance is positive and significant, and that liberal leadership both directly increases job performance and indirectly strengthens this effect through innovative behavior. The research aims to make a theoretical contribution to the literature by revealing the functionality of the liberal leadership approach in the context of innovation and performance.
Keywords: Liberal Innovation; Innovative Behavior; Job Performance; Leadership; Styles; Inovation